The relevance of financial development for economic growth: a bounds test approach - Wan Ngah, Wan Azman Saini; Habibullah, Muzafar Shah; Mohamed, Azali (Universiti Putra Malaysia Press, 2000)
The purpose of the study is to determine whether financial development is relevant for economic growth in Malaysia for the period 1955 to 1997. Using a bounds test proposed by Pesaran et al. (1996), our results suggest that using both linear and log-linear specifications, the data do not support the existence of long-run relationships between financial development and economic growth during the period under study.